Kajian Etnometodologi: Pola Pemasaran Berpihak Masyarakat Pedesaan Kediri Pada Ritel Tradisional - Samari Samari; Ema Nurzainul Hakimah (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2020)
This study aims to uncover and find out the meaning behind traditional retailer's marketing patterns, customer attitudes toward the application of these patterns and more in analyzing the interactions between traditional retailers and their customers and to learn the subjective norms that occur in these marketing patterns.This research is a qualitative research with ethnometodology approach. The study was conducted by direct observation and in-depth interviews with traditional retailers and their customers. Informants were selected with criteria 5 R occupying rural areas of Kediri, the chosen ones were Blabak village, Kandat district, Kediri district and Blabak village, Pesantren district, Kediri city. The observations themselves were made during the sale and purchase transactions at each traditional store, which then conducted open interviews to reveal the subjective norms that occur in the marketing pattern.Â The results of observations and in-depth interviews in this study indicate that the four dimensions of Hofstade's culture, namely Power Distance, Collectivism, Femininity, Uncertainty Avoidance develop positively where retailers place and make themselves as partners, brothers who empathize with customers by using a basic attitude of mutual trust for fluency fulfillment of each other's needs. The noble values of the culture of the people of Kediri in buying and selling "nya nggowo, podho mlakune" based on high trust give birth to stronger customer loyalty, especially when traditional retailers also practice the service quality dimension of reliability, assurance, tangibles, empathy and responsiveness.Keywords: cultural dimensions, traditional retailers, siding marketing patterns